Short range order structrures of lithium oxy-thiosilicophosphate glasses - Guantai Hu; Victor M. Torres, III; Steve W. Martin (Journal of Non-Crystalline Solids: X, 2023)
In this work, the compositional series of sulfide and mixed oxysulfide (MOS) glasses 0.56Li2S + 0.44[(0.33-x)PS5/2 + xPO5/2 + 0.67SiS2] was prepared, where 0 ≤ x ≤ 0.33, and their short range order (SRO) structures and their thermal properties have been investigated. Powder x-ray diffraction (XRD) confirmed that the MOS glasses were free from crystallization, with only very minor diffraction peaks in the x = 0 glass being observed. Fourier transform infrared (FT-IR), Raman, and 29Si and 31P magic angle spinning (MAS) NMR spectroscopies were used to identify the SRO structures present in these glasses. These spectra revealed oxygen migration from P to Si during synthesis. Although oxygen was introduced in the form of phosphorus oxide, the majority of the oxygen in these glasses ends up being bonded to silicon, thereby creating sulfur-rich SROs centered by phosphorus and MOS SROs centered by silicon. It was further found that the P-S SRO species were predominantly charged non-bridging sulfurs (NBS). The Si SRO species were comprised of neutral bridging oxygens (BOs) and charged non-bridging oxygens (NBOs) and neutral bridging sulfurs (BS) and charged non-bridging sulfurs with the neutral BO and BS species being larger in fraction than the NBO and NBS. These results suggest that the preponderance of the mobile Li+ cations in these glasses are located near the more negatively charged P centers and not near the more neutrally charged Si centers. The average negative charge of the P SRO structures was found to be ∼ − 3.0 with ∼97% of the phosphorous species in the P0 SRO while the average negative charge of the Si SRO structures was found to be −2.3. Consistent with the creation of the large numbers of NBS on the P and more BOs and BSs on the Si, these values are more negative and more positive, respectively, than the compositionally expected average value of −2.55. Differential scanning calorimetry (DSC) measurements of their glass transition (Tg) and crystallization (Tc) temperatures showed that the Tgs of these glasses are higher than 300 °C and their working ranges, ΔT ≡ Tc – Tg, are ∼100 °C.